(untitled) (MAUSAM, 1967)
The paper contains a preliminary study of the sea breeze at Thumba (08°32’ N, 76° 52’E) based on observations on 392 days, spread over a period of three years (1963-1966). Analysis on hourly wind observation reveals that the northeasterly or northerly land breeze is replaced by westerly or southwesterly sea breeze before mid-day during October to May it is also seen that November to April are favoured most by the sea breeze at Thumba. Southerly setting, late onset as well as early cessation of the sea breeze have been noticed on a few occasions. The wind is always above 5 kt after the incidence of the sea breeze and it may vary to a maximum speed of 22 kt and oscillates between 180°-300° depending on the prevailing synoptic situation. The vertical extent of the sea breeze is about 1 km and 0.8 km in summer and winter respectively. The frontal characteristics of the sea breeze are not very marked at Thumba. There is no significant temperature fall associated with the sudden onset of the see breeze, but slight rise in relative humidity is 5-10 percent recorded on a few occasions. The reversal of land and sea breeze is illustrated by an example giving hourly tower wind and pilot balloon wind data.